Extension of the transcriptional and translational map of the left end of the vaccinia virus genome to 21 kilobase pairs. - Cooper, J A (1981)
Physical, transcriptional, and translational maps of an EcoRI fragment located between 15,800 and 20,600 base pairs from the left end of the vaccinia virus genome were prepared. Major polypeptides with molecular weights of 14,000 (14K polypeptide), 32,000 and 38,000 were synthesized in a reticulocyte cell-free system programmed with immediate early RNA made in the presence of cycloheximide and selected by hybridization to lambda recombinant DNA containing the EcoRI fragment. With early RNA made in the presence of cytosine arabinoside, an inhibitor of DNA replication, the polypeptide pattern was similar except for quantitative differences in which less 38K polypeptide was detected as a translation product. With late RNA, isolated 6 h after infection without inhibitors, only traces of the early translation products were found and a new 40K polypeptide was detected. The size of the mRNA's for the 14K, 32K, and 38K polypeptides were determined to be approximately 760,880, and 1,150 nucleotides, respectively, by several independent procedures. Several large early RNAs not shown to code for any additional translation products were also detected. The size of the late message for the 40K polypeptide varied from 920 to 3,100 nucleotides. This heterogeneity appeared to be a general property of vaccinia virus late mRNA's. No evidence of RNA splicing was obtained by analysis of RNA-DNA hybrids after nuclease S1 treatment. Further analyses using separated recombinant DNA strands and restriction fragments indicated that all mRNA's were encoded by the leftward-reading DNA strand and at least two were overlapping. Since early and late mRNA's were encoded by the same DNA strand, the possibility of temporal regulation by transcriptional strand switching was eliminated. In conjunction with previous studies, a transcriptional map of the left 20,600 base pairs of the vaccinia virus genome was derived.